Phenomenon of Indirect Taxes Burden Transition in Palestine - Sakher Wa'el Mahmood El-Ahmed (My University, 2005)
Burden transition in Palestine this study aims at acquainting with the phenomenon of indirect taxes burden transition as one of the financial and taxation phenomena through the acting laws and regulations, in addition to the signed economical protocol handled between Israel government and the Palestinian liberation organization and mutual understandings between Israel and the Palestinian national authority. It also illustrates the different types or transition of taxation burden and theories related to this phenomenon and effective factors in them generally and dose related to the Palestinian case particularly in addition to evaluating those factors. Through this study, the researcher sought for the different kinds of taxes and the merits of every one, and he distinguished between the direct and indirect taxes. in defiled manner, he handled the indirect taxes in Palestine and the extent for their importance and participation in the general revenues for the Palestinian treasury. The study aimed at acquaintance with the taxpayer, and distinguished between the legal taxpayer the project aimed at laws enacting and the nominal taxpayer who is the actual bearer for taxation payer and the circumstances surrounding the process of taxation burden transition between the taxpayers and obligatory conditions to be spared for the competition of transition process. The researcher followed reviewing customs and tolls low no. 1 for the year 1962, and feel on the local products no. 16 for the year 1963 through the subjects related to this study. In addition to the paragraphs mentioned in the economical protocol or what is called Paris agreement related to indirect taxes and impart policies, and extent of their commitment with the parties signing the protocol in what was mentioned of articles, basis and ends which Israel imposed and which in still being fornicated. Through this study, the researcher aimed at submitting the most important problems concerned with the indirect taxes, that face the Palestinian national authority, and concentrated in infiltration the customs taxation revenues and Israel’s illusion. from duties and obligations confirmed on it according to the economical protocol and dealing mechanism with invoice of clearing invoice, and problems related to the laws and acting regulation and absence of Palestinian customs and tolls in addition non-activating the role of jurisdiction concerning these taxes, in addition to the problem of purchase tax and mechanism which it dealt with through the Palestinian customs and tolls with this problem. Then the Palestinian treasury became the actual bearer of harms and losses resulting from taxation burden transition normally and really because of taxation escape from one side, and the Israeli practices especially defining funds in the other side. The results showed that the phenomenon of indirect taxes burden transition is vital phenomenon reflects the economical. Legal. Legislative, political and social case to the axles. Of taxation system from a Palestinian national authority with its legislative, juridical and executive services and their various taxpayers and a law judging the relation among these dialoguing parties. but in the Palestinian case there is another party that negatively affects this phenomenon which is Israel and that considers the economical relation with it or through it is of the most important effective factors in that phenomenon, in addition to that relation is a fundamental cause for happening problems concerning the indirect taxes. The results also showed presence of Palestinian shortcoming in dealing with indirect taxes, and its transition phenomenon represented by the taxation legislator who didn’t give the necessary interest for enacting concerned laws in addition to the Palestinian jurisdiction which did quality neither jurisdiction cadre nor the concerned courts in taxes. The Palestinian negotiator who is not acquainted enough at the time of signing the agreements and what gaps happened in addition the taxpayers and whose illegal practices of taxation illusion with its en active effect on the phenomenon of the indirect taxes transition. Of what had been intentioned previously, the study recommend rations come out and reflected the necessity for a taxation system that touches the Palestinian ends and aims supported by related jurisdiction to end the stage of deal with the occupying heritage and the gaps in the agreements which those agreement imposed, in addition to taxation consciousness between taxpayers and their way dealing was with the indirect taxes burden transition that reflects the surrounding cir cum stances and effective factors and fosters the national economy and not in the current image that reflects their private tendency through their avoidance to commitment of debt burden wither they achieved its transition process or not.

هدفت هذه الدراسة الى التعرف على ظاهرة انتقال عبء الضرائب غير المباشرة كإحدى الظواهر المالية والضريبية, وذلك من خلال القوانين والأنظمة السارية، إضافة الى تناولها البروتوكول الاقتصادي الموقع بين حكومة دولة إسرائيل ومنظمة التحرير الفلسطينية، والتفاهمات ذات العلاقة ما بين إسرائيل والسلطة الوطنية الفلسطينية. كما وتوضح هذه الدراسة الأنواع المختلفة لانتقال عبء الضرائب والنظريات المتعلقة بهذه الظاهرة والعوامل المؤثرة فيها بصورة عامة وتلك المتعلقة بالحالة الفلسطينية بصورة خاصة, إضافة إلى تقييم تلك العوامل. وتطرق الباحث من خلال الدراسة إلى الأنواع المختلفة للضرائب وخصائص كل منها، وميز بين الضرائب المباشرة والضرائب غير المباشرة, وتناول بصورة تفصيلية أنواع الضرائب غير المباشرة في فلسطين ومدى أهميتها ومساهمتها في الإيرادات العامة للخزينة الفلسطينية. وهدفت الدراسة الى التعريف بالمكلف الضريبي، وميزت ما بين المكلف القانوني الذي استهدفه المشرع عند سن القوانين والمكلف الإسمي وهو الحامل الفعلي للعبء الضريبي، والظروف المحيطة بعملية نقل العبء الضريبي ما بين المكلفين والشروط الواجب توافرها لاكتمال النقل بإحدى صورها. وقد قام الباحث بمراجعة قانون الجمارك والمكوس رقم (1) لسنة 1962, ونظام الرسوم على المنتجات المحلية رقم (16) لسنة 1963 من خلال الأبواب ذات العلاقة بالدراسة, إضافة إلى المواد الواردة في البروتوكول الاقتصادي أو ما يعرف باتفاقية باريس، والمتعلقة بالضرائب غير المباشرة وسياسات الاستيراد، ومدى التزام الأطراف الموقعة على البروتوكول بما ورد فيه من المواد والأسس والغايات التي فرضتها إسرائيل وما زالت عند صياغة تلك الاتفاقية وتطبيقها. وهدف الباحث من خلال طرح الدراسة إلى طرح أهم المشكلات المتعلقة بالضرائب غير المباشرة والتي تواجه السلطة الوطنية الفلسطينية، وركزها في تسرب الإيرادات الضريبية الجمركية وعدم تنفيذ إسرائيل للواجبات والالتزامات المترتبة عليها وفقاً للبروتوكول الاقتصادي وآلية التعامل مع فاتورة المقاصة, وكذلك المشكلات المتعلقة بالقوانين والأنظمة السارية وعدم وجود قانون جمارك ومكوس فلسطيني، إضافة إلى عدم تفعيل دور القضاء ذو العلاقة بهذه الضرائب, أضف إلى ذلك مشكلة ضريبة الشراء والآلية التي تعاملت من خلالها الجمارك والمكوس الفلسطينية مع تلك المشكلة, وبالتالي اصبحت الخزينة الفلسطينية هي المتحمل الفعلي للأضرار والخسائر الناجمة عن عدم انتقال العبء الضريبي بصورة طبيعية وحقيقية بسبب التهرب الضريبي من جهة وبسبب الممارسات الإسرائيلية وأهمها حجز الأموال من جهة أخرى. وقد أظهرت النتائج أن ظاهرة انتقال عبء الضرائب غير المباشرة هي ظاهرة حيوية تعكس بالضرورة الحالة الاقتصادية والقانونية والتشريعية والسياسية والاجتماعية لمحاور النظام الضريبي من سلطة وطنية فلسطينية، بأجهزتها التشريعية والقضائية والتنفيذية, ومكلفين بأنواعهم، وقانون يحكم العلاقة فيما بين تلك الأطراف والمحاور, إلا أنه في الحالة الفلسطينية يظهر وجود طرف آخر يؤثر بصورة سلبية على تلك الظاهرة وهو إسرائيل، والتي تعتبر العلاقة الاقتصادية معها أو من خلالها من أهم العوامل المؤثرة في تلك الظاهرة إضافة إلى كون تلك العلاقة سبباً رئيسياً من أسباب وقوع مشكلات تتعلق بالضرائب غير المباشرة. وأظهرت النتائج أيضاً وجود تقصير ذاتي فلسطيني في التعامل مع الضرائب غير المباشرة وظاهرة انتقالها، تتمثل في المشرع الضريبي الذي لم يعط الاهتمام اللازم لسن القوانين ذات العلاقة إضافة إلى القضاء الفلسطيني الذي لم يؤهل الكادر القضائي ولا المحاكم المختصة في الضرائب, كذلك المفاوض الفلسطيني غير الملم بصورة كافي عند توقيعه للاتفاقيات وما ظهر فيها من الثغرات, ناهيك عن المكلفين بأنواعهم والذين لممارستهم غير المشروعة من تهرب ضريبي الأثر السلبي على ظاهرة انتقال عبء الضرائب غير المباشرة. ومما سبق خرجت توصيات الدراسة والتي تعكس الحاجة إلى وجود نظام ضريبي يلمس الغايات والأهداف الفلسطينية من وجوده، مدعماً بالقضاء ذي العلاقة لينهي مرحلة الإرث الاحتلالي والثغرات الموجودة في الاتفاقيات والحدود التي فرضتها تلك الاتفاقيات إضافة إلى ذلك نشر الوعي الضريبي ما بين المكلفين وكيفية تعاطيهم مع ظاهرة انتقال عبء الضرائب غير المباشرة بصورة تعكس الظروف المحيطة والعوامل المؤثرة وتعزز من الاقتصاد الوطني وليس بالصورة الحالية التي تعكس ميولهم الخاصة من خلال تجنبهم المشروع أو غير المشروع من الالتزام بعبء الدين الضريبي سواءً أتموا عملية نقله أم لم يقوموا بعملية النقل الضريبي اساساً.
ظاهرة انتقال عبء الضرائب غير المباشرة في فلسطين